Correlates of teachers ' attitudes towards and comfort about teaching school-based sexuality education in urban and rural Tanzania - Mkumbo, Kitila A. K. (Papers in Education and Development, 2018)
This study assessed teachers ' attitudes towards and comfort in teaching sexuality education within the school curriculum. Participants were drawn from one urban district and one rural district. The results show that a majority of teachers (more than 90%) in both districts overwhelmingly supported the provision of sexuality education in schools, as well the inclusion of a wide range of sexuality topics in the school curriculum. Nevertheless, though the results show that teachers may support the teaching of sexuality education and the inclusion of a number of topics in the school curriculum, they may not be comfortable and capable of teaching all the key sexuality education topics. This was particularly the case with regard to topics related to attitudes and values, such as homosexuality and other controversial topics. This implies that declaration of positive attitudes towards school-based sexuality education as well as change in policy alone may not be enough; these need to go hand in hand with providing teachers with the knowledge, skills and confidence to teach the various sexuality education topics. Key words: sexuality education, teachers, schools, attitudes and comfort